Petrophysical parameters of rocks of the Visean stage (Lokhvytsky zone of the Dnieper-Donets Depression) - S. Vyzhva; V. Onyshchuk; I. Onyshchuk; М. Orlyuk; V. Drukarenko; M. Reva; O. Shabatura (Геофизический журнал, 2019)
The results of complex investigations of petrophysical properties of the Visean rocks from wells in Lokhvytsky zone of the DDD (sandstones and siltstones from depths 5060―5600 m and limestones from depths 5960―6200 m) are presented. The open porosity coefficient, specific and relative electrical resistivity, velocity of P-waves and S-waves, three-dimensional magnetic susceptibility of rocks are determined. The studies of electric and acoustic properties were carried out in atmospheric and simulated stratal conditions on dry and water saturated stratal model rocks. Relative decrease of the porosity coefficient with changing from atmospheric conditions to reservoir conditions is from 5,5 to 25 % (mean 11,5 %). The average value of specific electrical resistivity of sandstones is 1.2 times more than of siltstones, and 12 times more than of limestones. It has been found that due to the closure of micro-cracks and the deformation of the pore space, the electrical resistance of rocks tends to increase with pressure. There is no significant distinction in velocity parameters between dry sandstones and siltstones, however, limestones are characterized by higher velocity (approximately 30 %) of transversal waves. Saturated rocks have approximately the same average values of S-wave velocity. The average value of velocity of S-waves in sandstones is 17 % higher than in siltstones. It was established that three-dimensional magnetic susceptibility varies in wide limits. Sandstones are characterized by the highest value, this parameter for limestones is 58 times lower than for sandstones. By the mean values of the physical parameters of sandstones and siltstones, there is clearly a direct relationship between the magnetic susceptibility, density and electrical resistivity, and the reverse one with porosity. The results obtained can be used to determine the perspectivity of rocks of different composition, to modeling their properties for different depths and to quantify the structure of their pore spaces. Received dependencies between the various parameters permit to clarify the interpretation of wells geophysical researching data of the studied area.